Does socialism really lead to economic failure? The USSR and COMECON Eastern Europe before 1989. (23rd February 2020) - Ball, Joseph
Abstract: The introduction of the market system in the COMECON countries of Europe after the end of communist rule is examined for the USSR and five Eastern European countries. The market system only led to improvements in economic performance relative to Western Europe in two out of six countries compared in 1988 and 2016. New figures from the Maddison Project Database are used to illustrate this. Quality of output problems in COMECON countries has probably been exaggerated. Evidence undermines claims that socialism leads to high investment for a low return in terms of economic growth. Investment may have been lower than official figures indicate. Economic growth may have been higher. Socialist countries that want higher growth than capitalist countries should invest more. Socialist societies can be established without necessarily sacrificing economic performance.